Long-acting cabotegravir and rilpivirine for HIV-1 suppression: switch to 2-monthly dosing after 5 years of daily oral therapy. (1st February 2022) - Mills, Anthony; Richmond, Gary J.; Newman, Cheryl; Osiyemi, Olayemi; Cade, Jerry; Brinson, Cynthia; De Vente, Jerome; Margolis, David A.; Sutton, Kenneth C.; Wilches, Viviana; Hatch, Sarah; Roberts, Jeremy; et al.
Abstract : Objectives: Long-acting formulations of cabotegravir (CAB) and rilpivirine (RPV) have demonstrated efficacy in Phase 3 studies. POLAR (NCT03639311) assessed antiviral activity and safety of CAB+RPV long-acting administered every 2 months (Q2M) in adults living with HIV-1 who previously received daily oral CAB+RPV in LATTE (NCT01641809). Design: A Phase 2b, multicenter, open-label, rollover study. Methods: LATTE participants with plasma HIV-1 RNA less than 50 copies/ml who completed at least 300 weeks on study were eligible. Participants elected to switch to either CAB+RPV long-acting Q2M or daily oral dolutegravir/RPV for maintenance of virologic suppression. The primary endpoint was the proportion of participants with HIV-1 RNA greater than or equal to 50 copies/ml at Month 12 (M12) per the Food and Drug Administration Snapshot algorithm. The incidence of confirmed virologic failure (CVF, two consecutive HIV-1 RNA measurements greater than or equal to 200 copies/ml), as well as safety, laboratory, and patient-reported outcomes (HIV Treatment Satisfaction and preference questionnaires) were also assessed. Results: Of 97 participants enrolled, 90 chose to receive CAB+RPV long-acting and seven chose dolutegravir/RPV. At M12, no participant had HIV-1 RNA greater than or equal to 50 copies/ml or met the CVF criterion in either treatment group. No new safety signals were identified. Total treatment satisfaction was high at Baseline and remained stable through M12 across both treatment groups. Overall, 88% ( n = 77/88) of long-acting arm participants preferred CAB+RPV long-acting to oral CAB+RPV. Conclusion: CAB+RPV long-acting maintained virologic suppression in participants who had previously received daily oral CAB+RPV for at least 5 years in LATTE, with a favorable safety profile. Most participants preferred CAB+RPV long-acting to their prior oral CAB+RPV regimen at M12. Abstract : Supplemental Digital Content is available in the text